High resolution melt analysis to confirm the establishment of Lactobacillus plantarum and Enterococcus faecium from silage inoculants during ensiling of wheat. (4th December 2015) - Ogiy, Svetlana; Chen, Yaira; Pasvolsky, Ronit; Weinberg, Zwi G.; Shemesh, Moshe
Abstract: High resolution melt (HRM) analysis is a sensitive post‐polymerase chain reaction (PCR) method that enables to distinguish between similar DNA sequences, because of its high resolution capability. Thus, we aimed to use the HRM analysis in order to identify species of lactic acid bacteria (LAB) used as inoculants for silage and to confirm their establishment during the ensiling of wheat. Four silage inoculants including Lactobacillus plantarum, Pediococcus pentosaceus, Enterococcus faecium and Lactobacillus buchneri were used as reference strains for HRM. The 16S rDNA gene of the four strains was amplified by real‐time PCR and the amplicons were used for subsequent HRM analysis. The different LAB species tested generated distinctive HRM profiles, allowing the discrimination and differentiation of each species. Two ensiling experiments were performed using wheat silages prepared in anaerobic jars. Treatments included control (no additives), L. plantarum and E. faecium each added at 10 6  colony forming unit per 1 g of fresh wheat. Three jars per treatment were sampled for analysis on different days of the experiment. Melting curves were obtained from DNA extracted from LAB colonies generated on de Man, Rogosa and Sharpe agar media. In Experiment 1, DNA was obtained from random colonies, whereas, in Experiment 2, in addition to random colonies, the rest of the colonies from a given plate were analyzed. In all experimental setups, when random colonies were used, the results indicated that different LAB species are present in the silage, which changes along with the decrease in pH during the ensiling of wheat. In Experiment 2, when all colonies were sampled from given plates, the dominance of the L .  plantarum showed up during ensiling of wheat, especially in wheat treated with L. plantarum . In summary, a simple molecular approach based on HRM analysis used in the present study, enables us to confirm establishment of L. plantarum throughout ensiling of wheat.